Determinan Status Kemiskinan Rumah Tangga Pertanian di Provinsi Nusa Tenggara Timur Tahun 2021 - I Gede Made Suwartana Dektana; Tiodora Hadumaon Siagian (Jurnal Sosial Ekonomi Pertanian, 2023)
Abstract The high percentage of poor households working in the agricultural sector in the province of East Nusa Tenggara (NTT) needs serious attention from the government, considering that the majority of NTT's population works in the agricultural sector. Therefore, it is crucial to study the determinants of the poverty status of agricultural households to provide input in overcoming the problem of poverty in NTT Province. By utilizing the March 2021 Socio-Economic Survey data and two analytical methods (descriptive and binary logistic regression), this study aims to obtain the characteristics of household heads who work in the agricultural sector and identify factors that influence poverty status of agricultural households in NTT Province. The results showed that the majority of household heads worked in the rice and secondary crops (71.8%), aged 40-59 years (52.13%), male (84.7%), graduated from elementary school/equivalent (42.41%), had less than 5 household members (53.34%), lived in rural areas (96.08%), and worked in informal sector (97.28%). While the results of binary logistic analysis showed that the variables that have a significant effect on the poverty status of the head of the agricultural household in NTT Province are place of residence, age of the head of the household, education level of the head of the household, number of household members, employment status of the head of the household, number of working hours of the head of household, have received credit assistance and have accessed the internet in the last three months. Keywords: Poverty Status; agricultural households; binary logistic regression; NTT